Design of wave-optical structured substrates for ultra-thin perovskite solar cells - Haque, Sirazul (2022)
grant agreement No 763989 UID/CTM/50025/2019 PTDC/NAN-OPT/28430/2017 PD/BD/143031/2018 SFRH/BD/148078/2019